1994
DOI: 10.1126/science.7510905
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Fas-Mediated Apoptosis by a Soluble Form of the Fas Molecule

Abstract: Fas is an apoptosis-signaling receptor molecule on the surface of a number of cell types. Molecular cloning and nucleotide sequence analysis revealed a human Fas messenger RNA variant capable of encoding a soluble Fas molecule lacking the transmembrane domain because of the deletion of an exon encoding this region. The expression of soluble Fas was confirmed by flow cytometry and immunocytochemical analysis. Supernatants from cells transfected with the variant messenger RNA blocked apoptosis induced by the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
685
4
16

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,034 publications
(731 citation statements)
references
References 19 publications
24
685
4
16
Order By: Relevance
“…Therefore, Fas-dependent apoptosis is a characteristic feature of the rheumatoid synovium. Cheng et a1 (8), however, recently reported the presence of elevated levels of sFas in sera from SLE patients, and they found that it exhibited inhibitory effects on Fas-dependent apoptosis in a mouse model of RA. On the other hand, recent studies by Owen-Schaub et al (17) and Weller et a1 (18) demonstrated sFas expression in anti-Fas-resistant tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Fas-dependent apoptosis is a characteristic feature of the rheumatoid synovium. Cheng et a1 (8), however, recently reported the presence of elevated levels of sFas in sera from SLE patients, and they found that it exhibited inhibitory effects on Fas-dependent apoptosis in a mouse model of RA. On the other hand, recent studies by Owen-Schaub et al (17) and Weller et a1 (18) demonstrated sFas expression in anti-Fas-resistant tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The method used to detect sFas mRNA is described in detail elsewhere (8). Briefly, synovial tissue was minced into small pieces and digested with collagenase (Sigma, St. Louis, MO) as previously described (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoform 2 is 314 amino acids in length and encodes three cysteine-rich regions and a death domain, but is missing a transmembrane region. Isoforms 4 through 7 are also missing a transmembrane region and these soluble isoforms of Fas receptor may sequester and inactivate Fas ligand on adjacent cells and infiltrating cytotoxic T lymphocytes [121]. Overexpression of soluble Fas receptor has been implicated with the progression of prostate cancer [122], Melanoma [123] and bladder cancer [124] and is known to antagonise Fas-receptor-mediated apoptosis in vitro [121].…”
Section: Modulators Of Fas Receptor and Fas Ligand Expressionmentioning
confidence: 99%
“…Human 4-1BB has two splice variants that produce soluble 4-1BB, which was enhanced in sera of rheumatoid arthritis, leukemia, and lymphoma patients (Furtner et al, 2005;Jung et al, 2004;Michel et al, 1998). Several members of the TNF receptor family, including TNF receptor, NGF receptor, CD27, CD30, GITR, and CD95, have been demonstrated to have soluble forms, which were generated by proteolytic cleavage and alternative splicing (Cascino et al, 1995;Cheng et al, 1994;Kohno et al, 1990;Nocentini et al, 2000;Pizzolo et al, 1990;Zupan et al, 1989). These soluble receptor forms antagonized the signaling through membrane-bound receptors (Cascino et al, 1996;Cheng et al, 1994;Kohno et al, 1990).…”
Section: Introductionmentioning
confidence: 99%